Pemanfaatan Bokashi Limbah Jerami Padi Terhadap Pertumbuhan dan Hasil Bayam Merah (Amaranthus tricolor L) - Raima, Eksi; Heiriyani, Tuti; Khamidah, Noor (Agroekotek View, 2023)
Rice production produces straw which has the potential to become waste which is not utilized properly. The presence of macro and micro nutrient content in rice straw waste has potential to be used as the main ingredient for making bokashi. Bokashi fertilizer is useful for consume green spinach because they are not very familiar with red spinach. Red spinach leaves contain high nutrients including carbohydrates, protein, fat, minerals, magnesium, iron, manganese, potassium, calcium and vitamins. The provision of rice straw bokashi is expected to increase the growth of red spinach plants. The purpose of this study is determine the effect of rice straw bokashi and an effective dose to increase the growth and yield of red spinach. Research techniques used in this study was a 1-factor randomized block design (RBD), namely the dose of rice straw bokashi consisting of 5 treatments with four repetitions, so that there were 20 experimental units. The traetment in this study is J0 = without giving rice straw bokashi, J1 = NPK (40 grams/bed), J2 = 4 tonnes/ha of rice straw bokashi (1.6 kg/bed), J3 = 5 tonnes/ha of rice straw bokashi (2 kg/bed), J4 = 6 tonnes/ha of rice straw bokashi (2.4 kg/bed). The results showed that the application of rice straw waste bokashi fertilizer affect the growth and yield of red spinach as indicated by the parameters of plant height, number of leaves, leaf area and wet weight with an effective dose found in treatment J4 = 6 tonnes/ha (2,4 kg/bed).